Detection of Deepfake using computer vision and deep learning - Rahman, Anisur; Uschash, Ehteshamul Islam; Rahman, Faria; Adiba, Shihaba Jamal Chowdhury; Labib, Tahmidul (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2023.